Cor ou Raça: Indígena? Contextos e Recepções da inclusão de uma categoria no Censo Demográfico 1991 - Ricardo Ventura Santos; Bruno Nogueira Guimarães; Alessandra Traldi Simoni (Confins)
The definition of categories in national Censuses is object of national and international disputes and socio-political dynamics, generating visibility and "legibility" to the issues represented therein. In 1991, the Brazilian Census included the category "indigenous" in its questionnaire, changing the description of the ethnic-racial composition of the Brazilian population. Thus, the objective of this article is to reflect on the context of the inclusion of the indigenous category in the 1991 Census and its reception, investigating some of the controversies generated in relation to the census operation and results generated by the census.